PENGARUH EDUKASI PENGETAHUAN PENYAKIT TUBERKULOSIS PARU DI SALAH SATU SEKOLAH KOTA PALEMBANG - Nur Afni (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: One of the health risks that adolescents may experience is exposure to infectious diseases such as tuberculosis. Lack of knowledge about TB is a major factor contributing to the rapid spread of TB, especially from adults with TB to children with poor immunity. Objective: To determine the relationship between gender and age and knowledge about TB among students before and after education. Methods: . A quantitative method with a cross-sectional design. The study population consisted of one class with 31 students, using total sampling. The study involved distributing leaflets and pre-test and post-test questionnaires before and after education. Results: Regarding gender, before education, 61.3% of males and 19.4% of females had good knowledge, while after education, this increased to 71% of males and 22.6% of females. The analysis of knowledge before education based on gender yielded a p-value of 1.000, indicating no significant relationship, with an OR of 1.579. Meanwhile, the analysis of knowledge after education yielded a p-value of 1.000, indicating no significant relationship, OR 0.917; 2) Before education, students aged 15 years had good knowledge at 64.5% and those aged 16 years at 16.1%, while after education, this increased to 77.4% for 15-year-olds and 16.1% for 16-year-olds. The analysis of knowledge before education based on student age yielded a p-value of 0.596, indicating no significant association, with an OR of 0.500. Meanwhile, the analysis of knowledge after education based on student age yielded a p-value of 0.045, indicating a significant association, OR 1.400. Conclusion: Health education programs using audiovisual materials and direct lectures can enhance knowledge about tuberculosis in school settings.